Designing and manufacturing the arad rescue robot and evaluating its efficiency for usar missions - Sharifibamrood, M.; Mafi, M. (Наука та інновації, 2020)
Introduction. Every year, natural disasters such as earthquakes, floods, and storms occur around the world and many people die as a result of the devastation. In the relief and rescue operations, many injured people may lose their lives as they remain under the rubble for hours and even days because rescue agents have no access to them.
Problem Statement. One of the major problems for rescuers is overcoming and removing obstacles on the path for quick access to injured people.
Purpose. To study the process of designing the Arad rescue robot for urban search and rescue (USAR), to define the robot tasks, and to design suitable mechanisms for their fulfillment. The general purpose is to design and to build a rescue robot with a high speed and precision and a low cost in order to better find the injured people under the rubble.
Materials and Methods. To complete the design method, CATIA software was used to apply the finite element method for powerful analysis of complicated parts. Also, Solidworks was used to model the mechanisms, where 3D sketch of each component of the robot was generated by means of it. Finally, the components are convened together with controlling hardware. Two central processors are used within the control system of the robot. The director's PC as the master processor and the laptop installed on the robot as the vassal processor. The general design of the robot has been performed using the SOLIDWORK modeling software while to design the robot arm, CATIA software is employed so that the manipulator motion analysis is made in this software in addition to using the software modeling power. In order to pass obstacles and impassable routes, a caterpillar has been used in the robot motion system and also, two arms have been embedded in the front part of the robot to climb obstacles and rugged terrains.
Results. In addition to the rotating arm, one skilled arm has been designed for robot to overcome these problems. In addition, the use of sand wheels has forced the robot to increase its ability to travel on different routes.
Conclusions. Different national and international competitions have provided an opportunity for this robot to display its capabilities in an environment close to the real conditions. The robot has been awarded with many titles, which testifies to a great success and actual improvements in every aspect. The performance of this design and build has been shown in the Rescue Robots League and appreciated as one of the best designs. Вступ. Щороку стихійні лиха (землетруси, повені, буревії тощо) трапляються по всьому світу та тягнуть за собою
загибель багатьох людей. Часто рятувальні місії не можуть вчасно надати допомогу і постраждалі залишаються під
завалами тривалий час.
Проблематика. Однією з головних проблем для рятувальників є подолання та усунення перешкод для забезпечення
швидкого доступу до травмованих людей, які знаходяться під завалами.
Мета. Розробити та створити рятувального робота з високою швидкістю та точністю роботи та з низькою вартістю
для забезпечення оперативного знаходження та рятування поранених під завалами.
Матеріали й методи. Для проектування використано програмне забезпечення CATIA із застосуванням методу
кінцевих елементів для потужного аналізу складних деталей; для моделювання механізмів, за допомогою яких
створювалися 3D ескізи кожного компонента робота, — програмне забезпечення SOLIDWORKS. В єдину систему
компоненти складено з використанням керуючого обладнання.
Результати. У системі управління роботом використано два центральних процесори — керівний ПК, як головний процесор, і ноутбук, встановлений на робота, як залежний процесор. Загальну конструкцію робота виконано з використанням програмного забезпечення для моделювання SO LIDWORKS , тоді як для проектування роботи механізму — програмне забезпечення CATIA ATIA . Щоб подолати складні маршрути, в системі руху робота застосовано гусеницю, а в передню частину робота вбудовано дві «руки» для підйому на перешкоди та нерівні місцевості. Окрім руки, яка обертається, розроблено ще одну робочу руку, використання якої дозволило підвищити здатність робота проходити різними маршрутами.
Висновки. На національних та міжнародних змаганнях було продемонстровано можливості робота в умовах, близьких до реальних. Розробка отримала багато нагород, що свідчить про успіх та фактичні вдосконалення в кожному аспекті його роботи. Ефективність конструкції робота було доведено в Лізі рятувальних роботів, де розробку було оцінено як одну з найкращих конструкцій.